Shear strength and hardness of two tropical wood species as function of heat treatment - Yusoh, Alia Syahirah; Sabaruddin, Fatimah Athiyah; Md Tahir, Paridah; Lee, Seng Hua; Mohd Khairun Anwar, Uyup; Husain, Hamdan; Ghani, Aizat; Hiziroglu, Salim (Universidad del Bio-Bio, 2022)
The aim of this study was to evaluate the effect of heat treatment on surface roughness, shear strength and hardness of two tropical wood species, namely batai (Paraserainthes falcataria) and sesendok (Endospermum malaccensis). Samples were exposed to temperature levels of 120 ºC and 180 ºC for 3 h and 6 h. The surface quality of the control and heat-treated samples were determined using a stylus technique. Hardness and shear strength of the samples were evaluated using Janka hardness and block-shear test, respectively. The results reveal that the surface roughness of batai improved 3 % for 80-grit and 5 % for 180-grit samples while surface roughness of sesendok improved 7 % and 10 % for 80-grit and 180-grit, respectively by the increase of the heat temperature and prolonged durations. Analysis of variance (ANOVA) also revealed that most of the tested properties on the treated wood were significantly affected by the species, girt number and also temperature. In contrast to the untreated wood species, the heat-treated wood species exhibited lower values of shear strength and hardness. Overall, the hardness and shear of both species were adversely influenced by heat exposure.